Interactive Learning Innovation in Archival Material Through the Development of Augmented Reality-Based E-Modules - Susan Trinoviorar; Ismet; Syarifuddin (Universitas Pendidikan Ganesha, 2024)
The lack of specific teaching materials and adequate textbooks for archival subjects can hinder the student learning process and optimally achieve the Independent Curriculum's objectives. Based on this, this study aims to develop an AR-based e-module on archival material. This type of research uses the Alessi & Trollip development model, which includes the stages of planning, design, and development. The research subjects are material experts, design experts and media experts. The subjects of the research trial involved students. Data collection methods were carried out through interviews, surveys, and tests. The data collection instrument used a questionnaire sheet. Data analysis techniques used qualitative and quantitative descriptive analysis. The effectiveness test used N-gain. The results showed that the AR-based e-module developed was very valid, with a validity score of 83% based on expert review. Practical with a score of 80.14% on the practicality test. The N-gain result was 0.67, which is included in the moderate category. There was a significant increase in student learning outcomes before and after using the AR-based E-module. It was concluded that the augmented reality-based e-module can significantly improve student learning outcomes. The research implies that the augmented reality-based e-module that was developed can be used in learning activities for vocational high school students.